2012
DOI: 10.1080/19942060.2012.11015447
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Factors Influencing Type B Thoracic Aortic Dissection: Computational Fluid Dynamics Study

Abstract: Thoracic aortic dissection is a dangerous pathological condition where blood intrudes into the vascular wall, creating an artificial channel, the false lumen. The weakened false lumen wall may rupture, resulting in high mortality. Biomechanical factors investigated are the size of the dissecting aneurysm, the blood pressure, the geometry around the distal tear, a configuration of partial thrombosis, the distance between the tears, and the shear stress. The force acting on the walls of the false lumen will gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The simulations were performed following a protocol similar to those previously described in the literature [ 13 , 14 ]. The unsteady solver in Fluent was used to solve the three-dimensional fluid flow as governed by the continuity equation and the Navier-Stokes equations.…”
Section: Methodsmentioning
confidence: 99%
“…The simulations were performed following a protocol similar to those previously described in the literature [ 13 , 14 ]. The unsteady solver in Fluent was used to solve the three-dimensional fluid flow as governed by the continuity equation and the Navier-Stokes equations.…”
Section: Methodsmentioning
confidence: 99%
“…(Rudenick et al, 2010). Geometric considerations such as tapering of the aorta are commonly overlooked (Rudenick et al, 2010;Hou et al, 2010;Fan et al, 2010), and some studies even opt to omit the supraaortic branches (those branching off from the aortic arch) (Fan et al, 2010;Tang et al, 2012;Rudenick et al, 2010). However, such idealised models are rare in the literature, perhaps due to the scepticism of the clinical community.…”
Section: Biomechanics Of Aortic Dissectionmentioning
confidence: 99%
“…Accurate prediction of disease progression, for example, whether imminent rupture or dilation would occur, has a substantial clinical impact as it helps to determine the timing of surgical/intervention treatment for a patient [16]. In a clinical study performed across 101 patients with type B acute dissection without complications, Marui et al [51] reported that a maximum aortic diameter of >40 mm and a patent false lumen during the acute phase serve as important predictors for aortic enlargement in the chronic phase.…”
Section: Numerical Simulations In Aortic Dissectionmentioning
confidence: 99%